Treatment Outcomes of Colistin- and Carbapenem-resistant Acinetobacter baumannii Infections: An Exploratory Subgroup Analysis of a Randomized Clinical Trial. (20th November 2018) - Dickstein, Yaakov; Lellouche, Jonathan; Ben Dalak Amar, Maayan; Schwartz, David; Nutman, Amir; Daitch, Vered; Yahav, Dafna; Leibovici, Leonard; Skiada, Anna; Antoniadou, Anastasia; Daikos, George L; Andini, Roberto; et al.
Abstract: Background: We evaluated the association between mortality and colistin resistance in Acinetobacter baumannii infections and the interaction with antibiotic therapy. Methods: This is a secondary analysis of a randomized controlled trial of patients with carbapenem-resistant gram-negative bacterial infections treated with colistin or colistin-meropenem combination. We evaluated patients with infection caused by carbapenem-resistant A. baumannii (CRAB) identified as colistin susceptible (CoS) at the time of treatment and compared patients in which the isolate was confirmed as CoS with those whose isolates were retrospectively identified as colistin resistant (CoR) when tested by broth microdilution (BMD). The primary outcome was 28-day mortality. Results: Data were available for 266 patients (214 CoS and 52 CoR isolates). Patients with CoR isolates had higher baseline functional capacity and lower rates of mechanical ventilation than patients with CoS isolates. All-cause 28-day mortality was 42.3% (22/52) among patients with CoR strains and 52.8% (113/214) among patients with CoS isolates ( P = .174). After adjusting for variables associated with mortality, the mortality rate was lower among patients with CoR isolates (odds ratio [OR], 0.285 [95% confidence interval CI, .118–.686]). This difference was associated with treatment arm: Mortality rates among patients with CoR isolates were higher in those randomized to colistin-meropenem combination therapy compared to colistin monotherapy (OR, 3.065 [95% CI, 1.021–9.202]). Conclusions: Colistin resistance determined by BMD was associated with lower mortality among patients with severe CRAB infections. Among patients with CoR isolates, colistin monotherapy was associated with a better outcome compared to colistin-meropenem combination therapy. Clinical Trials Registration: NCT01732250 Abstract : In a retrospective analysis of a randomized controlled trial, infection with carbapenem-resistant, colistin-resistant Acinetobacter baumannii was associated with lower mortality than carbapenem-resistant, colistin-susceptible Acinetobacter . Colistin-carbapenem combination therapy was associated with higher mortality than colistin monotherapy in patients with colistin-resistant isolates.